Study of grape seed compounds (Vitis vinifera) by using high-performance liquid chromatography (HPLC) technique and studying the inhibitory activity of plant extracts against bacteria isolated from urinary tract infections. (Journal of the College of Basic Education, 2022)
A qualitative chemical detection of the active compounds was carried out in the phenolic extract of grape seeds, using the high performance liquid chromatography technique. A chemical detection of the aqueous and alcoholic grape seed extracts was carried out using several detection methods, and the results showed the presence of many active compounds, including phenols, terpenes, steroids, and flavones. (40.80) mg/mL each separately in the growth of Pseudomonas aeruginosa and Klebsiella pneumonia.